Irisin response to acute moderate intensity exercise and high intensity interval training in youth of different obesity statuses: A randomized crossover trial. Issue 4 (28th February 2022) - Colpitts, Benjamin H.; Rioux, Brittany V.; Eadie, Ashley L.; Brunt, Keith R.; Sénéchal, Martin
Abstract: Limited data exist regarding the impact of an acute bout of exercise with varying intensities on irisin levels in the youth of different obesity statuses. The objectives were to (1) compare an acute bout of moderate continuous intensity (MCI) exercise and an acute bout of high‐intensity interval training (HIIT) on irisin response in youth with different obesity statuses and, (2) investigate whether changes in irisin levels are correlated with exploratory outcomes. A randomized crossover design study was conducted on 25 youth aged 12–18 years old. Participants were classified as either healthy weight (BMI percentile <85; n  = 14) or overweight/obese (BMI percentile ≥85; n  = 11). Participants performed an MCI exercise session at 50% of heart rate reserve for 35 min and a HIIT exercise session for 35 min, with intervals every 5 min increasing from 50% heart rate reserve to 85–90% for 2 min. Irisin was measured using an enzyme‐linked immunoabsorbent assay from plasma sampling obtained throughout the exercise (at times 0, 7, 14, 21, 28, and 35 min). A time effect was observed throughout the HIIT session [ F (1, 5) = 6.478, p  < 0.001]. Bonferonni post‐hoc analysis revealed significant differences in irisin levels post‐exercise (35 min) compared to times 7, 14, 21, and 28 min. Irisin increased during HIIT (81.0% ± 71.3; p  = 0.012) in youth with a healthy weight. No differences were observed for youth living as overweight or with obesity. Overall, HIIT elicits a higher peak irisin response compared to MCI exercise training in youth. Abstract : High‐intensity interval training elicits a higher irisin response compared to moderate continuous‐intensity exercise in youth.